The Effect of an Educational Program Based on the Van Hiele Model on Developing Visual Culture of Contemporary Arts among Students of the Art Education Department - Hussein Rishk Khdier; suhad Jawad Faraj Al-Sakani; Mohammed Jasem Al-Obaidi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
The current research aimed to identify the effect of an instructional program based on the Van Hiele model in developing visual culture of contemporary arts among students of the Department of Art Education. To achieve this, the researcher adopted the experimental method with a design based on two equivalent groups (experimental and control). A sample of (60) male and female students was selected from a research population of (332) first-year students in the Department of Art Education, College of Basic Education, Al-Mustansiriyah University.To measure this effect, the researcher developed a visual culture test consisting of (20) items, which was administered before and after the application of the instructional program. The findings revealed that the program had a significant effect in enhancing the visual culture of the students in the subject of contemporary arts.Based on this, the most important conclusion reached by the researcher is that the Van Hiele model stimulated students’ abilities to perceive ideas, exchange opinions, acquire knowledge and understanding, and consolidate information in their minds, thereby producing individuals capable of inference. Accordingly, the researcher recommended adopting the instructional program based on the Van Hiele model in teaching contemporary art trends to first-year students in the Department of Art Education, College of Basic Education, University of Misan. The researcher also suggested conducting a correlational study to examine the relationship between academic achievement and visual culture among students of the Colleges of Fine Arts in Iraq.DOI: https://doi.org/10.54633/2333-025-058-023